2021
DOI: 10.4012/dmj.2020-390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multi-components released from S-PRG filler on the activities of human dental pulp-derived stem cells

Abstract: Numerous studies have shown that the sustained release of ions from dental restorative materials have acid buffering capacity, prevents tooth enamel demineralization, and inhibits bacterial adhesion. Herein, the release behavior and bioresponsiveness of ions released from surface pre-reacted glass-ionomer (S-PRG) fillers were investigated in different types of media based on human dental pulp-derived stem cell (hDPSC) responses. The hDPSCs were cultured for 1-7 days in S-PRG eluates diluted with varying amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…These results suggest that ALP activity increases according to the B concentration. Ishigure et al 24) reported that ALP activity of hDPSC increased with the addition of the S-PRG filler eluate, which contained a higher amount of B than other ions. The results in this study suggest that S-PRG filler-derived B contributes to an increase in ALP activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results suggest that ALP activity increases according to the B concentration. Ishigure et al 24) reported that ALP activity of hDPSC increased with the addition of the S-PRG filler eluate, which contained a higher amount of B than other ions. The results in this study suggest that S-PRG filler-derived B contributes to an increase in ALP activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the comparison between E3 and the control medium showed the cell proliferation effect and ALP activity decreased in E3 compared with the control, despite that the concentration of B in the medium was almost the same. Ishigure et al 24) reported that the hDPSC proliferation was promoted in the medium where the S-PRG filler eluate has been added, probably due to the larger amount of Sr compared with other ions. As above, the presence of the cell proliferation effect and ALP activity decreased in E3 in comparison with the control medium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, composite resins containing bioactive fillers based on surface pre-reacted glass (S-PRG) technology, which can continuously release multiple ions such as fluoride (F − ), sodium (Na + ), strontium (Sr 2+ ), silicate (SiO 3 2− ), borate (BO 3 3− ), and aluminum (Al 3+ ) ions, are being used as pit and fissure sealants. The mechanism underlying S-PRG technology is known to involve an acid–base reaction between fluoroboraluminosilicate glass and polycarboxylic acid, resulting in material biofunctionality [ 8 ]. Previous research has demonstrated that dental products containing S-PRG fillers can prevent tooth enamel demineralization [ 9 ] and provide acid-buffering ability [ 10 ] because of the constant release of these ions.…”
Section: Introductionmentioning
confidence: 99%